Journal of Water Resources Planning and Management (Virginia : ASCE, 2020)
u
u
u
u
u
u
u
u
u
u
u
u
Unraveling the Effects of Long-Distance Water Transfer for Ecological Recharge -- Review of Utilization Management of Groundwater at Risk of Salinization -- Operational Seasonal Water Supply and Water Level Forecasting for the Laurentian Great Lakes -- Multiobjective Scheduling Method for Short-Term Peak Shaving Operation of Cascade Hydro Plants -- Balancing Ecological Requirements and Power Generation in Reservoir Operation in Fish Spawning Seasons -- Ecological Optimal Operation of Hydropower Stations to Maximize Total Phosphorus Export -- Regularization of an Inverse Problem for Parameter Estimation in Water Distribution Networks -- Resolving Conflicts between Irrigation Agriculture and Ecohydrology Using Many-Objective Robust Decision Making -- Case Study on Hydropolitics in Afghanistan and Pakistan: Energy and Water Impacts of Kunar River Development -- Pressure-Based Analysis of Water Main Failures in California -- Hourly and Daily Urban Water Demand Predictions Using a Long Short-Term Memory Based Model -- Need for Process Based Empirical Models for Water Quality Management: Salinity Management in the Delaware River Basin.
Includes bibliographical references.